The Most Cited Original Articles in Brain Imaging of Children With Cerebral Palsy: A Bibliometric Analysis Between 1984 and 2019 - Wu, Fan; Wang, Xiaoyu; Li, Xianjun; Jiang, Haoxiang; Huang, Tingting; Liu, Congcong; Wang, Miaomiao; Zhai, Zhonghui; Zhang, Xiaoman; Zhang, Jingjing; Liu, Heng; Yang, Jian (Frontiers in Neurology, 2020)
Abstract Objective: Brain imaging is important in diagnosing children with cerebral palsy (CP) and in identifying its etiology. To provide study navigation in this field, a bibliometric analysis was conducted by analyzing the most highly cited articles. Methods: The Web of Science All Databases were used for literature search in this study. All original articles on imaging in children with CP were searched. Two reviewers screened the search results independently and eliminated articles based on exclusion criteria such as participants over 20 years old, topics referring to images outside of the brain, or trauma. According to descending order of yearly citation counts, the top 25% of all included articles were considered as highly cited articles. Information such as yearly citations, research purposes, imaging modalities, CP types, and study designs were recorded and analyzed. Results: A total of 50 highly cited articles ranked by yearly citations (from 23.85 to 3.33, 1991-2018) were included in this study. Considering different research purposes, these studies were classified into three categories: diagnosis studies (n=25; 1991–2017, median: 2011), mechanism studies (n=15; 1999–2018; median: 2014), and prognosis and therapeutic effect studies (n=10; 2008–2017; median: 2014.5). First, for diagnosis studies, 22 studies used single modality and three used multi-modalities; the majority of these studies focused on diagnostic value evaluation (n=10) and image performance (n=12) of a single type of CP (n=15) by using descriptive (n=14) or cross-sectional approaches (n=10). Second, for mechanism studies, the ratio between single and multi- modality was 8:7; most of these studies concentrated on a single subtype spastic CP (hemiplegia=10, quadriplegia=2) with cross-sectional study design (n=10). Third, regarding the prognosis and therapeutic effect studies, the single verses multi- modality ratio was 5:5, and these studies were dedicated to the efficiency of constraint-induced movement therapy in children with hemiplegia; paired design trials (n=6) and randomized controlled trials (n=2) were used more frequently. Conclusion: Studies using multi-modality and high-level evidence-based design to provide information regarding mechanism, prognosis and therapeutic efficacy may be the potential future research direction in the field of CP research.